A model for selecting IT outsourcing strategy: the case of e-banking channels. Issue 2 (3rd April 2018) - Hanafizadeh, Payam; Zare Ravasan, Ahad
ABSTRACT: Information Technology Outsourcing (ITO) is a good strategy for firms in general and banking institutions, in particular to reduce operating costs and improve competitiveness, but it remains complex for businesses to scientifically select the appropriate ITO strategy. In this paper, after doing an in-depth literature review, based on the technology, organization, and environment (TOE) framework, 23 factors are identified as influencing factors on e-banking channels' outsourcing decision. To test the research hypotheses, the Partial Least Squares (PLS) technique is utilized. The results illustrated that 17 out of 23 assumed factors influence banking outsourcing decisions. A fuzzy TOPSIS model using supported factors is proposed to solve the ITO decision problem. Throughout this step, we used data from a real Iranian banking case to demonstrate the applicability of the method for evaluating five possible outsourcing options for five e-banking channels. The validity of the rankings is assessed through experts' opinions in which they were satisfied by the proposed priority even for the two of the channels where different strategies from the bank's current practices were proposed. The experts believed that regarding the situation of the channels, the bank itself and the surrounding environment, the bank could benefit more from suggested strategies than currently adopted ones for these two channels.